2010
DOI: 10.1089/cbr.2010.0820
|View full text |Cite
|
Sign up to set email alerts
|

In VitroandIn VivoEvaluation of64Cu-Radiolabeled KCCYSL Peptides for Targeting Epidermal Growth Factor Receptor-2 in Breast Carcinomas

Abstract: Epidermal growth factor receptor-2 (EGFR-2) has been implicated in the pathogenesis of breast and other carcinomas. In this report, we tested the ability of a bacteriophage selected peptide KCCYSL, radiolabeled with 64 Cu, to image EGFR-2 expressing breast tumors in vivo by positron emission tomography (PET). We evaluated and compared the in vivo tissue distribution and imaging properties of 64 Cu-X-(Gly-Ser-Gly)-KCCYSL peptide (X ¼ 1,4,7,10, tetraazacyclododecane-N,N',N'',N'''-tetracetic acid, [DOTA] 1,4,8, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…8,9 The P6.1 peptide, derivatized with different metal chelators (DOTA, NOTA, CB-TE2A, DAP) and labeled with radionuclide metal ions ( 111 In, 64 Cu, 99m Tc), has been successfully used for in vivo imaging of HER-2 overexpressing tumor models. [10][11][12][13] Single-positron emission computed tomography/computed tomography studies showed that radioconjugated peptides were able to accumulate specifically at the tumor site, with K d ranging from 30 to 45 nM, with minimal nonspecific retention in other organs. This peptide sequence has also been proposed for the selective delivery of supramolecular carriers such as copolymeric micelles 14 or pH-tunable liposomes 15 for diagnostic or therapeutic applications.…”
Section: Ringhieri Et Almentioning
confidence: 99%
“…8,9 The P6.1 peptide, derivatized with different metal chelators (DOTA, NOTA, CB-TE2A, DAP) and labeled with radionuclide metal ions ( 111 In, 64 Cu, 99m Tc), has been successfully used for in vivo imaging of HER-2 overexpressing tumor models. [10][11][12][13] Single-positron emission computed tomography/computed tomography studies showed that radioconjugated peptides were able to accumulate specifically at the tumor site, with K d ranging from 30 to 45 nM, with minimal nonspecific retention in other organs. This peptide sequence has also been proposed for the selective delivery of supramolecular carriers such as copolymeric micelles 14 or pH-tunable liposomes 15 for diagnostic or therapeutic applications.…”
Section: Ringhieri Et Almentioning
confidence: 99%
“…Phage binding affinity may be evaluated by comparing the number of infectious units (TU/mL) between the cancerous and normal cell lines. In order to analyze the binding affinities of peptides outside of the phage environment, biotinylated or radiolabeled peptides may be synthesized and used in in vitro/in vivo binding studies [62,73].…”
Section: New Ovarian Cancer Cell Targeting Peptidesmentioning
confidence: 99%
“…As described above, selected phage clones may be further analyzed for their binding affinity by micropanning experiments in which phage are incubated with normal ovarian cancer cells and ovarian CSC. Once high binding clones have been identified, biotinylated or radiolabeled peptides can be synthesized and analyzed for their tumor targeting abilities [62,73]. Peptides with high binding affinity for CSC will most likely not be applicable as imaging agents due to the low percentage of CSC in a tumor.…”
Section: New Ovarian Cancer Stem Cell (Csc) Targeting Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the present studies, L19K-FDNB was modified to incorporate 1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA) at the peptide's N terminus (NO2A). We radiolabeled the peptide with 64 Cu ( 64 Cu half-life 5 12.7 h; b 1 5 17.8%, E max 5 653 keV; b 2 5 38.4%, E max 5 578 keV), because 64 Cu-NOTA complexes are stable in vitro and in vivo (18)(19)(20). We hypothesized the radiolabeled irreversible peptide agent 64 Cu-L19K-FDNB would improve tumor uptake, compared with its reversibly binding peptide analogs 64 Cu-L19K-(2,4-dinitrophenyl) (64Cu-L19K-DNP) and 64 Cu-L19K.…”
mentioning
confidence: 99%